JAK-STAT-activated, fratricide-resistant CAR-T cells targeting membrane-bound TNF effectively treat AML and solid tumors - Yang Li; Taeko Hayakawa; Shinsuke Iida; Toshiaki Yoshikawa; Yusuke Ito; Satoshi Inoue; Yuichi Ishikawa; Takahiro Nakashima; Tetsuya Matsukawa; Hitoshi Kiyoi; Yuki Kagoya; Hitomi Kasuya; et al. (Journal for ImmunoTherapy of Cancer)
Background While chimeric antigen receptor (CAR)-T cell therapy exhibits a robust therapeutic efficacy against B-cell malignancies and multiple myeloma, its efficacy and safety have not been established for acute myeloid leukemia (AML) and solid tumors due to the paucity of established target antigens. Some AML and solid tumor cells express tumor necrosis factor (TNF), which is initially expressed on the cell surface prior to shedding.Methods In this study, we obtained monoclonal antibodies against the N-terminal fragment of TNF (TNF-NTF) that remains on the cell surface after shedding. We then generated CAR-T cells to target TNF-NTF using the antibody sequence. To enhance the therapeutic efficacy of TNF-NTF CAR-T cells, we further engineered the previously developed chimeric cytokine receptor consisting of GP130, IL6R, and constitutively active IL7R with the M452L mutation (G6/7R).Results TNF-NTF CAR-T cells efficiently lysed TNF-expressing leukemia cells in vitro, while showing limited antitumor efficacy in vivo due to poor expansion and persistence. Activated T cells upregulate TNF, which was recognized by TNF-NTF CAR-T cells and led to fratricide. Genetic knockout (KO) of TNF significantly enhanced the viability and proliferation of TNF-NTF CAR-T cells, while slightly reducing their cytotoxic activity. In addition, ectopic expression of G6/7R improved the effector function of TNF-NTF CAR-T cells through constitutive activation of janus kinase (JAK)-signal transducers and activators of transcription (STAT) signaling. The G6/7R-expressing TNF-KO TNF-NTF CAR-T cells exhibited superior persistence and durable antileukemic efficacy in vivo compared with parental CAR-T cells. We also confirmed that TNF-NTF CAR-T cells can target primary AML cells, including a leukemia-initiating population with colony-forming capacity. Unlike CD33, targeting TNF-NTF did not show cytotoxicity against normal hematopoietic stem/progenitor cells. Finally, we demonstrated the curative efficacy of G6/7R TNF-KO TNF-NTF CAR-T cells against TNF-expressing ovarian tumor cells in vivo.Conclusions Our studies highlight TNF-NTF as a promising cell surface target for CAR-T cell therapy that can be applied to AML as well as solid tumors.